2003
DOI: 10.1530/eje.0.1490583
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous sex hormones in men aged 40-80 years

Abstract: Objective: To determine the relationship between aging, life-style factors and health-related factors and endogenous sex hormone levels. Design: Cross-sectional study of 400 independently living men between 40 and 80 years of age. Methods: After exclusion of subjects who were not physically or mentally able to visit the study center, 400 men were randomly selected from a population-based sample. Total testosterone (TT), bioavailable testosterone (BT) (i.e. not bound to sex hormone-binding globulin (SHBG)), SHB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
250
11
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(318 citation statements)
references
References 50 publications
51
250
11
6
Order By: Relevance
“…Higher BMI and waist circumference are associated with lower total, bioavailable or free testosterone and SHBG. 6,7,[144][145][146] The association between higher BMI and lower total testosterone appears more consistent that between BMI and free testosterone. 146,147 Smoking, lower alcohol intake and physical activity or vigorous exercise are factors associated with higher total testosterone and SHBG levels.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 76%
See 2 more Smart Citations
“…Higher BMI and waist circumference are associated with lower total, bioavailable or free testosterone and SHBG. 6,7,[144][145][146] The association between higher BMI and lower total testosterone appears more consistent that between BMI and free testosterone. 146,147 Smoking, lower alcohol intake and physical activity or vigorous exercise are factors associated with higher total testosterone and SHBG levels.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 76%
“…146,147 Smoking, lower alcohol intake and physical activity or vigorous exercise are factors associated with higher total testosterone and SHBG levels. 6,7,147 However, other studies have not confirmed these associations. 148,149 It is important to note the severe damaging effects of smoking on cardiovascular and respiratory health far outweigh any possible benefit it may confer on testosterone levels.…”
Section: Testosterone Cardiovascular Risk and Mortality In Aging Menmentioning
confidence: 96%
See 1 more Smart Citation
“…8 In one cross-sectional study of 400 communitydwelling men ages 40-80 years, increases in both BMI and central adiposity (waist circumference) were associated with low levels of T, BT, and dehydroepiandrosterone sulfate, whereas both current smoking and greater physical activity were associated with higher T concentrations. 14 Some grossly obese patients have reduced total T and SHBG levels, as well as diminished T-SHBG binding, such that FT levels remain normal. 11,22 Obesity may lower circulating androgens or reduce T-SHBG binding via (1) excessive metabolic clearance of androgens in adipose tissues; 11 (2) aromatization of androgens in adipose tissues; or (3) increased formation of inflammatory cytokines (eg tumor necrosis factor-a, interleukin-1b), which may also blunt secretion of LH and gonadotropin-releasing hormone (GnRH).…”
Section: Obesitymentioning
confidence: 99%
“…smoking, alcohol use, physical activity, obesity and pretreatment serum lipids, and thus cannot draw any firm conclusions about their possible effect in these patients. However, from previous reports, moderate alcohol consumption decreases the risk of AMI and might be associated with an increased plasma oestradiol level [12,29], whereas a low endogenous oestradiol level might increase the risk of AMI by lowering the high-density lipoprotein level before the onset of the therapy [30].…”
Section: P L a S M A O E S T R A D I O L L E V E L A N D L O W R I S mentioning
confidence: 87%